2019
DOI: 10.1002/iub.2182
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes and cancer: From oncogenic roles to therapeutic applications

Abstract: Exosomes belong to extracellular vehicles that were produced and secreted from most eukaryotic cells and are involved in cell‐to‐cell communications. They are an effective delivery system for biological compounds such as mRNAs, microRNAs (miRNAs), proteins, lipids, saccharides, and other physiological compounds to target cells. In this way, they could influence on cellular pathways and mediate their physiological behaviors including cell proliferation, tumorigenesis, differentiation, and so on. Many research s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 247 publications
(375 reference statements)
0
31
0
Order By: Relevance
“…EVs derived from different TME components, including TEC, influence key aspects of cancer growth/progression, and have recently been recognized as being of great importance for tumor targeting 44 . The goal of this study was to investigate whether IL-3Rα blockade on TEC impacts tumor progression via EVs.…”
Section: Discussionmentioning
confidence: 99%
“…EVs derived from different TME components, including TEC, influence key aspects of cancer growth/progression, and have recently been recognized as being of great importance for tumor targeting 44 . The goal of this study was to investigate whether IL-3Rα blockade on TEC impacts tumor progression via EVs.…”
Section: Discussionmentioning
confidence: 99%
“…Several different molecules and proteins are involved in exosome production and secretion [10][11][12]. Much evidence exists for the important role of these vesicles in intercellular communications and their involvement with both pathological and physiological conditions [13,14]. Exosomes have also been implicated in intracellular communication, angiogenesis, immune system modulation and metastasis progression in cancer [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Much evidence exists for the important role of these vesicles in intercellular communications and their involvement with both pathological and physiological conditions [13,14]. Exosomes have also been implicated in intracellular communication, angiogenesis, immune system modulation and metastasis progression in cancer [15][16][17][18]. The techniques used to isolate and enrich exosomes from biological samples include precipitationultracentrifugation and ultracentrifugation followed by differential gradient centrifugation [6,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, accumulated knowledge of characteristics and cargos of EVs has suggested that these structures could serve as valuable biomarkers for diagnostic/prognosis, as well as therapeutic agents for treatment of various pathologies [ 200 ]. The emergence of EVs in cancer therapy serves as a valuable nanotechnology to overcome major worldwide cancer management problems [ 201 ]. Currently, there are many studies recommending use of EVs as delivery vectors for treatment of various cancer, following manipulation and engineering of these EVs to carry various molecules useful as therapeutic agents ( Figure 4 ) [ 61 , 202 , 203 ].…”
Section: Evs Used In Anti-cancer Therapymentioning
confidence: 99%